Pengaruh Model Pembelajaran Kooperatif Tipe Two Stay Two Stray (TSTS) dengan Media Pembelajaran terhadap Aktivitas dan Hasil Belajar Siswa SMAS Bina Bangsa Simpang Gambus - Sari, Nada Aprilia; Febriani, Husnarika; Rasyidah, Rasyidah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the effect of the Two Stay Two Stray (TSTS) cooperative learning model with learning media on student activities and learning outcomes in the human respiratory system material in class XI IPA SMAS Bina Bangsa Simpang Gambus for the 2020/2021 academic year. This research is a quantitative research with a Quasi Experimental design. The samples in this research were class XI IPA-A as the experimental class and class XI IPA-B as the control class. Data analysis used to determine student learning activities is by using the TCR (Respondent Achievement Level) formula and for student learning outcomes data analysis uses statistical hypothesis testing. The results of the research show that there are differences in student learning activities and student learning outcomes in the two classes. For learning outcomes, students obtained an average posttest score for the control class, namely 70, while the average posttest score for the experimental class was 84.4. Based on the results of observations of learning activities and student learning outcomes, there is an influence of the use of the Two Stay Two Stray type cooperative learning model with learning media where student learning activities in the experimental class > control class, so that Ha is accepted. Obtaining student learning outcomes through statistical hypothesis testing shows that the tcount value is 7.28 and the ttable price is 2.068, meaning tcount>ttable, so Ha is accepted.